2016
DOI: 10.4103/0253-7613.194864
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic activity of aqueous extract of Camellia sinensis in rats

Abstract: Objectives:The present study was undertaken to evaluate anxiolytic effect of Camellia sinensis (CS) and possible mechanism on acute and chronic administration in rats.Materials and Methods:Eight groups of rats with six in each group were used. Group I served as control. Group II received diazepam (1 mg/kg). Groups III, IV, and V received CS in doses of 3.3, 16.5, and 33 mg/kg, respectively. Three pharmacologically validated experimental models – elevated plus maze (EPM), light and dark box (LDB), and open fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The pathophysiology underlying anxiety disorders is mostly associated with the dysfunction of GABAergic neurotransmission [ 77 ]. In our study, we observed that the treatment of animals with DZP decreases locomotor activity, which agrees with results reported by other researchers [ 67 ]. DZP and other benzodiazepine drugs act as positive allosteric modulators of the GABA A receptor complex.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pathophysiology underlying anxiety disorders is mostly associated with the dysfunction of GABAergic neurotransmission [ 77 ]. In our study, we observed that the treatment of animals with DZP decreases locomotor activity, which agrees with results reported by other researchers [ 67 ]. DZP and other benzodiazepine drugs act as positive allosteric modulators of the GABA A receptor complex.…”
Section: Discussionsupporting
confidence: 93%
“…Locomotor activity is a sign of alertness, and a decline in it implies a drop in CNS excitability [ 64 , 66 ]. Treatment with DPZ reduced the locomotor activity in the anxious test mice [ 67 , 68 ], resulting in calming behaviors [ 69 ]. Findings from this investigation showed that treatment of animals with DPZ and TFA significantly reduces locomotor activity, resulting in a diminution in movement and calming behaviors, as demonstrated by the reduction in square crosses, rearing, and grooming.…”
Section: Discussionmentioning
confidence: 99%